CMG configuration and Steering Approach for Spacecraft Rapid maneuvers. Issue 1 (2016) - Ashok, K; Aditya, R; Joglekar, Harish K; Siva, MS; Philip, NK
Abstract: Earth observation satellites require rapid attitude maneuvering and stringent pointing accuracy for imaging payloads. This paper presents a configuration with Control Moment Gyros (CMG) and Steering scheme for rapid maneuvering of Indian spacecrafts. The maneuver considered is of track-to-track, where the spacecraft has an initial non-zero angular rate and perform the attitude maneuver to achieve the target imaging rate. Iterative algorithm is used for computing the maneuver time between various imaging targets. The CMG steering for avoiding the singularities during the time-optimal maneuvers has been addressed for meeting the stringent attitude control requirements. The Gain switching controller has been designed for high tacking performance during maneuver and imaging. The CMG steering approach, Maneuver control algorithms for on-board implementation is demonstrated by simulations.